Review of investigational medical devices' clinical trials and regulations in Africa as a benchmark for new innovations - Matovu, Brian; Takuwa, Mercy; Mpaata, Charles Norman; Denison, Fiona; Kiwanuka, Noah; Lewis, Steff; Norrie, John; Ononge, Sam; Muhimbise, Owen; Tuck, Sharon; Etuket, Maureen Dimitri; Ssekitoleko, Robert T. (Frontiers in Medical Technology, 2022)
Medical technologies present a huge potential in improving global health playing a key role towards achieving Sustainable Development Goal 3 by 2030. A number of clinicians, innovators, business entities and biomedical engineers among others have developed a number of innovative medical devices and technologies to address the healthcare challenges especially in Africa. Globally, medical devices clinical trials present the most acceptable method for determining the risks and benefits of medical device innovations with the aim of ascertaining their effectiveness and safety as compared with established medical practice. However, there are very few medical device clinical trials reported in Africa compared to other regions like USA, UK and Europe. Most of the medical device clinical trials reported in Africa are addressing challenges around HIV/AIDS, maternal health and NCDs. In this mini review, we report about some of the published medical device clinical trials in Africa PubMed and Google Scholar and their associated challenges.